2020
DOI: 10.31234/osf.io/9rbcs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How To Kill A Greek God - A Review, Critique, and Meta-Analysis of 14 years of Proteus Effect Research

Abstract: The Proteus Effect is a phenomenon whereby a user of a virtual environment temporarily adopts attitudes and behaviours that are consistent withstereotypes associated with the appearance of their avatar.A recent meta-analysis (Ratan et al, 2019) estimates that the strength of the Proteus Effect is "small to medium" under the de facto descriptors of Cohen (1992). Ratan et al also suggest some meta-analytic regressors which may moderate the overall effect. In this replication and extension of Ratan et al’s review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…It should be noted that using negative stereotypes relating to race, gender, or body size has been criticized for its lack of consideration of the sensitive nature of these topics (Clark, 2020 ). Using avatars to highlight the existence of harmful stereotypes is not inconsiderate in itself.…”
Section: Proteus Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that using negative stereotypes relating to race, gender, or body size has been criticized for its lack of consideration of the sensitive nature of these topics (Clark, 2020 ). Using avatars to highlight the existence of harmful stereotypes is not inconsiderate in itself.…”
Section: Proteus Effectmentioning
confidence: 99%
“…Interestingly, based on this description, the framework generally makes opposite predictions to the Proteus effect (Clark, 2020 ). Indeed, the Proteus effect assumes that embodying an avatar will cause the user to adopt behaviors that would be coherent with any stereotypes associated with the avatar's appearance.…”
Section: Further Theoretical Hypothesesmentioning
confidence: 99%
“…To avoid redundancy the following four publications summarizing authors' previous work are not reported in Table 2: Buisine et al ( 2017), de Sousa (2015), Guegan et al (2019), andClark (2020).…”
Section: Notementioning
confidence: 99%
“…Ten publications addressed the impact on the creativity of embodying an avatar, including six original studies (Table 2), three book chapters summarizing previous authors’ publications (Buisine et al, 2017; de Sousa, 2015; Guegan et al, 2019), and one a review (Clark, 2020). The main research questions were:…”
Section: User’s Embodiment By An Avatar: a Vr Specific Feature Suppor...mentioning
confidence: 99%
“…Some studies also pointed to the potential effect of virtual appearance manipulation to reduce pain perception [31,42]. The Proteus Effect [12,61], in which embodied users temporarily adopt behaviors related to stereotypes associated with the altered appearance of their avatar was also shown to induce change in behaviour [62] and self-identification [50]. Homoncular Flexibility suggests that it is possible for users to learn to control virtual bodies different from their own.…”
Section: Dysmorphic Embodiment In Vrmentioning
confidence: 99%